The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00299-004-0813-z
|View full text |Cite
|
Sign up to set email alerts
|

The rice metallothionein gene promoter does not direct foreign gene expression in seed endosperm

Abstract: We generated transgenic tobacco and rice plants harboring a chimeric gene consisting of the 5'-upstream sequence of the rice metallothionein gene (ricMT) fused to the beta-glucuronidase (GUS) gene. The activity and tissue-specific expression of the ricMT promoter were demonstrated in these transgenic plants. In the transgenic rice plants, despite substantial levels of GUS activity in the shoot and root, almost no GUS signal was detected in the endosperm. Thus, the ricMT promoter could be useful in avoiding acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…These results are consistent with other reports that Cd tolerance and accumulation in sugarcane is mediated by other mechanisms [29]. OsMT1b has greater affinity for Cd and Ni ions compared to Zn and Cu ions, suggesting that OsMT1b may protect rice cells against toxic metals, or play a role in detoxification [23,30]. The over-expression of sheep MTII and maltose binding protein in the cytoplasm of E. coli allowed the bioaccumulation of the heavy metals such as Zn2?, Cu2?…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are consistent with other reports that Cd tolerance and accumulation in sugarcane is mediated by other mechanisms [29]. OsMT1b has greater affinity for Cd and Ni ions compared to Zn and Cu ions, suggesting that OsMT1b may protect rice cells against toxic metals, or play a role in detoxification [23,30]. The over-expression of sheep MTII and maltose binding protein in the cytoplasm of E. coli allowed the bioaccumulation of the heavy metals such as Zn2?, Cu2?…”
Section: Discussionsupporting
confidence: 94%
“…Plant type 1 MTs are more abundantly expressed in roots than leaves, whereas type 2 MTs are expressed primarily in leaves and at a lower level in roots [10,12,14,18,22,23]. Type 3 MTs are expressed in leaves or in ripening fruit [24], whereas type 4 MTs appear to be restricted to developing seeds [25].…”
Section: Discussionmentioning
confidence: 94%
“…During the 2-3 days after sowing, the gene encoding metallothionein was upregulated. Metallothionein is reported to be involved in metal translocation (Fukuzawa et al 2004;Zhou et al 2006), suggesting that metal translocation is important during seed germination. One day after sowing, the genes for amylase and enzymes involved in reduction and were upregulated (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It has thus been suggested that these MRE or MRE-like sequences may be involved in heavy metal responsiveness. However, to our knowledge, to date there is no evidence showing MRE or MRE-like sequence confers heavy metal responsiveness to these plant genes (Evans et al, 1990;Whitelaw et al, 1997;Fukuzawa et al, 2004;Perry et al, 2005). Thus, MRE-like sequences in plants may be involved in other forms of regulation.…”
Section: The Function Of the Mre-like Sequence In Plantsmentioning
confidence: 99%